Chemical Surface Grafting of Pt Nanocatalysts for Reconciling Methanol Tolerance with Methanol Oxidation Activity. Issue 8 (17th March 2023) - Lenne, Quentin; Mattiuzzi, Alice; Jabin, Ivan; Troian‐Gautier, Ludovic; Hamon, Jonathan; Leroux, Yann R.; Lagrost, Corinne
Abstract: A conceptual challenge toward more versatile direct methanol fuel cells (DMFCs) is the design of a single material electrocatalyst with high activity and durability for both oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR). This requires to conciliate methanol tolerance not to hinder ORR at the cathode with a good MOR activity at the anode. This is especially incompatible with Pt materials. We tackled this challenge by deriving a supramolecular concept where surface‐grafted molecular ligands regulate the Pt‐catalyst reactivity. ORR and MOR activities of newly reported Pt‐calix[4]arenes nanocatalysts (Pt CF 3 ${{_{{\rm CF}{_{3}}}}}$ NPs/C) are compared to commercial benchmark PtNPs/C. Pt CF 3 ${{_{{\rm CF}{_{3}}}}}$ NPs/C exhibit a remarkable methanol tolerance without losing the MOR reactivity along with outstanding durability and chemical stability. Beyond designing single‐catalyst material, operable in DMFC cathodic and anodic compartments, the results highlight a promising strategy for tuning interfacial properties. Abstract : Reconciling the Irreconcilable through a supramolecular concept : surface functionalization with a monolayer of organic calix[4]arene ligand of Pt nanoparticles enables to keep Pt electrocatalytic efficacy for ORR with methanol tolerance in the presence of 0.5 m methanol without losing MOR reactivity.